Pengaruh Perbandingan Tepung Beras Hasil Perkecambahan Gabah dan Tepung Penja Terhadap Penerimaan Organoleptik Snack Bar: The Effect of Comparison of Grain Germinated Rice Flour and Penja Fish Flour on The Organoleptic Accaptance of Snack Bar - Nur Afni Azis; Rizka Aulia Safarni; Rosmiati (Universitas Djuanda, 2026)
This study aims to develop and evaluate the effect of the ratio of penja flour (Sicyopterus spp.) and germinated rice flour on the organoleptic acceptance of local snack bars. Three formulations were tested: P1 (20% penja flour : 80% germinated rice flour), P2 (50% penja flour : 50% germinated rice flour) and P3 (80% penja flour : 20% germinated rice flour). Sprouted rice flour was made by soaking and fermenting until sprouts reached 0.1–0.2 cm; penja flour was obtained from steamed and dried penja fish; snack bars were baked (100°C for 60 minutes, then 120°C for 20 minutes). Organoleptic tests were conducted by 25 moderately trained panelists using a 1-5 hedonic scale (1 = strongly dislike to 5 = strongly like) for the attributes of color, aroma, taste, texture, and overall acceptance. The results showed that the flour composition had a significant effect on all sensory attributes; formulation P1 gave the highest scores for color (3.50), aroma (3.43), taste (3.33), texture (3.07), and overall acceptance (3.57), while P3 gave the lowest scores (overall acceptance 2.33). Formulation P1 (20% penja flour : 80% germinated rice flour) was more accepted by the panelists and has the potential to be developed as a nutritious local snack bar. Keywords:grain germination rice flour, penja fish flour, snack bar, organoleptic